Respuesta :
Answer:
x = -2,4
(disclaimer plugging in -2 will give an imaginary number)
Step-by-step explanation:
3[tex]\sqrt{x^2-7}[/tex]=3[tex]\sqrt{2x+1}[/tex]
Divide both sides by 3
[tex]\sqrt{x^2-7}[/tex]=[tex]\sqrt{2x+1}[/tex]
Square both sides to cancel square roots
[tex]x^2-7=2x+1[/tex]
Move all the terms to the left side
[tex]x^2-2x-8=0[/tex]
Use the quadratic formula
[tex]x=\frac{2 +/- \sqrt{(-2)^2-4(1)(-8)}}{2(1)}[/tex]
which gives x= -2,4
OR factor the quadratic
(x-4)(x+2)=0
x= -2,4
Answer:
part one is cube
part two is x=8.25
Step-by-step explanation:
on edge 2022